Effect of Easel Leaf Extract (Lannea coromandelica) on the Amount of Trichodina sp in Lele Dumbo Fish (Clarias gariepinus) - Sri Rahayu; Safrida Safrida; Asiah M.D; Khairil Khairil; Supriatno Supriatno (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
Trichodiniasis was an infection of Trichodina sp included in one of the ectoparasites that can interfere with the cultivation of African catfish. Trichodina sp is easy to attack fish that have soft body morphology and do not have scales like African catfish. Trichodiniasis control that was commonly done by farmers was to use antibiotics or chemicals. The leaves of the horses (Lannea coromandelica) are medicinal plants that have anti-parasitic properties that can be used as natural medicines, because they contain bioactive compounds such as flavonoids, tannins, and terpenoids. The purpose of this study was to determine the effect of easel leaf extract on the amount of Trichodina sp. The type of research used is experimental, with a quantitative approach. The experimental design used in the study was CRD (Completely Randomized Design.) consisting of 4 replications and 6 treatments. The treatment in this study using extract of horses with the concentration of the treatment was negative control (P0) without easel leaf extract, 1000 ppm (P1), 2000 ppm (P2), 3000 ppm (P3), 4000 ppm (P4), and control positive with the administration of acriflavine 1 ml (P5). The data obtained were analyzed using Analysis of Variant (ANOVA) and DMRT (Duncan Multiple Range Test.) testing. The results showed the value of Fcount Ftable = 37.58 2.77 with a test level α = 0.05. The results obtained were the administration of easel leaf extract significantly affected the amount of Trichodina sp. Keywords: African catfish, Trichodina sp, Lannea coromandelica Trichodiniasis merupakan infeksi.Trichodina sp termasuk ke dalam salah.satu. ektoparasit yang dapat menganggu budidaya ikan lele dumbo. Trichodina sp mudah menyerang ikan yang memiliki morfologi tubuh lunak dan tidak memiliki sisik seperti ikan lele dumbo. Pengendalian Trichodiniasis yang umum dilakukan petani adalah menggunakan antibiotik atau bahan-bahan kimia. Daun kuda-kuda (Lannea coromandelica) merupakan tumbuhan obat yang memiliki sifat anti parasit yang dapat. digunakan.sebagai obat.alami., karena mengandung.senyawa bioaktif seperti flavonoid, tanin, dan terpenoid. Pelaksanaan penelitian ini bertujuan untuk mengetahui pengaruh ekstrak daun kuda-kuda terhadap jumlah Trichodina sp. Jenis penelitian yang digunakan adalah eksperimental, dengan pendekatan kuantitatif. Adapun. rancangan percobaan.yang digunakan dalam penelitian.adalah RAL (Rancangan. Acak.Lengkap.) yang terdiri atas 4 kali ulangan dan 6 perlakuan. Perlakuan pada penelitian menggunakan ekstrak kuda-kuda dengan konsentrasi perlakuan adalah kontrol negatif  (P0) tanpa ekstrak daun kuda-kuda, 1000 ppm (P1), 2000 ppm (P2), 3000 ppm (P3), 4000 ppm (P4), dan kontrol positif dengan pemberian antibiotik acriflavine 1 ml (P5). Data.yang diperoleh dianalisis.menggunakan.Analisis Varian (ANAVA) dan dilakukan pengujian DMRT (Duncan Multiple Range Test.). Hasil penelitian menunjukkan nilai Fhitung Ftabel = 37,58 2,77 dengan taraf uji α = 0,05. Hasil yang dieroleh ialah pemberian ekstrak daun kuda-kuda berpengaruh.nyata terhadap jumlah Trichodina sp. Kata kunci: Lele dumbo, Trichodina sp, Lannea coromandelica